Integrating network pharmacology and experimental verification to explore the mechanism of puerarin against oliguria in acute alcoholism - Wan, Mei-Xuan; Huang, Xian-Jun; Li, Xue; Suan, Juan; Xu, Li (Frontiers in Pharmacology, 2022)
Abstract Purpose: This study was designed to evaluate the pharmacological mechanisms of puerarin against oliguria in acute alcoholism via network pharmacology analysis combined with experimental verification. Methods: First, this study established an acute alcoholism rat model, compared the changes in urine volume in each group, and observed the therapeutic effect of puerarin by H&E staining, biochemical, RT-qPCR and immunohistochemical. Second, puerarin-related targets were searched in the TCMS, PubChem, CNKI, Wanfang, PubMed and GeenMedical Academic databases. And potential disease targets were obtained from the GeneCards, MalaCards and NCBI-gene database, and genes with puerarin target genes intersections were screened out. The interaction network for co-predicted targets was obtained using the STRING database, and core targets were imported into Cytoscape for visualization using DAVID Bioinformatics Resources 6.8. The essential genes were subjected to the Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) pathway enrichment analyses to predict related biological processes and significant signaling pathways. Finally, molecular docking was used to examine the interaction of puerarin with key targets, and the core targets were validated further by RT-qPCR and western blot. Results: Compared to the model group, the urine volume of the rats was significantly increased after puerarin treatment , and the levels of antidiuretic hormone (ADH) and aquaporin 2 (AQP2) expression were decreased. Searching the intersection of puerarin and acute alcoholism targets yielded 214 potential targets, 837 biological processes and 185 signaling pathways involved. The molecular docking results indicated a good affinity between puerarin and key targets (cyclic adenosine monophosphate (cAMP), protein kinase A (PKA), cAMP-response element binding protein (CREB), c-Fos). RT-qPCR and western blot further verified that puerarin could down-regulate the expression of cAMP/PKA/CREB/c-Fos. Conclusion: This study identified the potential targets of puerarin against oliguria in rats with acute alcoholism using network pharmacology and animal experiments. The mechanism may be closely related to the cAMP signaling pathway.